Partial discharge pattern recognition based on EEMD singular value entropy - Luo Riping; Luo Yingting; Lai Shiyu; Zhao Xianyang; Wang Liqi (Dianzi Jishu Yingyong)
Aiming at the non-stationary of gas insulatede switchgear(GIS) partial discharge fault signal and the low accuracy of discharge type recognition, a partial discharge pattern recognition method based on ensemble empirical mode decomposition(EEMD) singular value entropy is proposed. Firstly, the EEMD algorithm is used to decompose the original signals of partial discharge to intrinsic mode functions(IMFs), according to the mean square error, kurtosis and euclidean distance evaluation index, the optimal modal component with most implicit discharge information is selected for signal reconstruction. Secondly, the singular value decomposition is performed on the reconstructed signal, and the singular value entropy is calculated in combination with the information entropy algorithm. Finally, according to the singular value entropy, the type of GIS partial discharge is distinguished. The experiment results show that by comparing with the traditional EMD singular value entropy and VMD singular value entropy algorithms, the method in this paper can effectively identify the discharge type through the singular entropy values in different intervals.